Charge Pumping Strategy for Rotation and Sliding Type Triboelectric Nanogenerators. Issue 21 (16th April 2020) - Bai, Yu; Xu, Liang; Lin, Shiquan; Luo, Jianjun; Qin, Huaifang; Han, Kai; Wang, Zhong Lin
Abstract: Triboelectric nanogenerator (TENG) is an emerging approach for harvesting energy from the living environment. But its performance is limited by the maximum density of surface charges created by contact electrification. Here, by rationally designing a synchronous rotation structure, a charge pumping strategy is realized for the first time in a rotary sliding TENGs, which is demonstrated to enhance the charge density by a factor of 9, setting up a record for rotary TENGs. The average power is boosted by more than 15 times compared with normal TENGs, achieving an ultrahigh average power density of 1.66 kW m −3, under a low drive frequency of 2 Hz. Moreover, the charge pumping mechanism enables decoupling of bound charge generation and the severity of interfacial friction in the main TENG, allowing surface lubricants to be applied for suppressing abrasion and lowering heat generation. The adaptability of the strategy to rotation and sliding type TENGs in low‐frequency agitations provides a breakthrough to the bottleneck of power output for mechanical energy harvesting, and should have a great impact on high‐power TENG design and practical applications in various fields. Abstract : A charge pumping strategy is realized for the first time in rotary triboelectric nanogenerators (TENGs) using a synchronous charge pump to generate bound charges. The charge density is enhanced by a factor of 9, and the power output is boosted by more than 15 times. The strategy could greatly promote practical applications of TENGs in high‐power self‐powered systems and environment energy harvesting.